1996
DOI: 10.1074/jbc.271.5.2762
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding and Dimerization of the Fe−S-containing FNR Protein from Escherichia coli Are Regulated by Oxygen

Abstract: The transcription factor FNR from Escherichia coli regulates transcription of genes in response to oxygen deprivation. To determine how the activity of FNR is regulated by oxygen, a form of FNR had to be isolated that had properties similar to those observed in vivo. This was accomplished by purification of an FNR fraction which exhibited enhanced DNA binding in the absence of oxygen. Iron and sulfide analyses of this FNR fraction indicated the presence of an Fe-S cluster. To determine the type of Fe-S cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
303
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(316 citation statements)
references
References 32 publications
9
303
2
Order By: Relevance
“…This sequence matches the known consensus binding site for the oxygenresponsive transcriptional regulator FNR (16,41). FNR directly senses a range of low-oxygen conditions and binds to DNA to either repress genes required for aerobic growth or activate those needed for growth under low-oxygen conditions (28,35).…”
Section: Resultsmentioning
confidence: 99%
“…This sequence matches the known consensus binding site for the oxygenresponsive transcriptional regulator FNR (16,41). FNR directly senses a range of low-oxygen conditions and binds to DNA to either repress genes required for aerobic growth or activate those needed for growth under low-oxygen conditions (28,35).…”
Section: Resultsmentioning
confidence: 99%
“…They may mediate electron transfer as in the ferredoxins; they may be structural elements, as in E. coli endonuclease III (24);, or they may be at the active site of enzymes, as in aconitase. More recently, some [4Fe-4S] centers have been found to be important for the control of gene expression (25)(26)(27). The discovery of the ferredoxin-like [2Fe-2S] clusters in the SoxR protein, which controls an oxidative stress regulon, immediately suggested that these groups are the redox sensor for the regulon and that the ability of SoxR to serve as a 2 J. Wu and B. Weiss, unpublished result.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor FNR from Escherichia coli regulates transcription of genes in response to oxygen deprivation due to a Fe-S cluster in the wild-type protein that is extremely oxygen labile. Anoxically purified FNR was mostly a dimer with high DNA-binding activity compared to that of the aerobically purified FNR monomer [40]. The protein SoxR, a homodimer containing two (2Fe-2 S) clusters, is both a sensor of oxidative stress and a transcriptional regulator.…”
Section: Discussionmentioning
confidence: 99%